Implementation of Household Approach v'iews from Key Informants' : Case of Chalwita Model Village, Rumphi, Malawi - Mbakaya, Beatrice; Ndengu, Dominique; Njela, Dalo (Journal of Agricultural Extension Management, 2018)
Household Approach is one of the extension approaches being advocated in Malawi for promoting the participation of all gender categories in farm planning and management. Adopting an interpretivist’s view, this pilot study assessed the implementation of Household Approach in the Rumphi district, Malawi. Data was collected through face-to-face interviews using a checklist. In addition, documents, including reports and farmers’ record books, were analysed and focus group discussions were arranged to triangulate data. Household Approach implementation in Mhuju, Rumphi, was carried out by using a model village as a special interest group. The study has established that all stakeholders are aware of the Household Approach, however, many Household Approach tools were not adequately articulated among frontline staff and local facilitators. Joint planning and implementation of farming activities were observed among the targeted population after the implementation of Household Approach. Some resistance was noticed from male partners on women gaining access to and control over resources; however there is a steady move towards equal access and control of resources across all gender categories